Preliminary effectiveness of mHealth app-based pelvic floor muscle training among pregnant women to improve their exercise adherence: a pilot randomised control trial - Jaffar, Aida; Mohd Sidik, Sherina; Foo, Chai Nien; Muhammad, Noor Azimah; Abdul Manaf, Rosliza; Suhaili, Nazhatussima (MDPI, 2022)
This pilot randomised control trial (RCT) aimed to evaluate the feasibility and preliminary effectiveness of conducting a full-powered trial for a newly developed pelvic floor muscle training (PFMT) app among pregnant women with urinary incontinence (UI) in Malaysia. This was a prospective, single-centre, single-blind, parallel, randomised controlled, pilot feasibility study—the Kegel Exercise Pregnancy Training app (KEPT app) trial. In total, 26 pregnant women with urinary incontinence from an urban healthcare clinic were recruited and randomly assigned to either intervention or waitlist control group. The intervention group received the KEPT app, while the control group received usual antenatal care (waitlist control). Of the 26 pregnant women, 16 (61.5%) completed the two-month follow-up. The recruitment rate was 54.2%, and the retention rate was 62.5% in the intervention group and 60% in the control group. There was a significant difference between intervention and control groups’ baseline measurement in the severity of UI (p = 0.031). The app improved their knowledge (p = 0.011) and self-efficacy (p = 0.038) after the first month and attitude (p = 0.034) after two months of intervention, compared with the control group. This study supports the feasibility of our future cluster RCT. The KEPT app demonstrates a promising effect in improving PFMT attitude and self-efficacy and potentially enhancing exercise adherence among pregnant women with UI. Trial registration: This study was prospectively registered on ClinicalTrials.gov on 19 February 2021 (NCT04762433).